Mempersiapkan Akuntan Muda di Era TUNA: Pengaruh Kesiapan Teknologi dan Persepsi Terhadap Adopsi AI - Khairany, Saskia Jamilah; Salim, Julian Stevanus; Putri, Karin Chlarista; Agustina, Trifena (Ekonomis: Journal of Economics and Business, 2025)
This study aims to understand how technological readiness influences the adoption of artificial intelligence technology among accounting students, by examining the role of perceived technology use as a mediating variable. A quantitative approach was used by distributing a 26-item questionnaire online to 244 accounting students from several universities in Palembang City. The sampling technique used was random sampling. Data analysis used hierarchical regression with partial least squares structural equation modeling (PLS-SEM). The results showed that technological readiness significantly positively influenced the adoption of artificial intelligence technology in the accounting field. In addition, a mediation analysis revealed that perceived technology use was able to partially mediate the relationship between technological readiness and adoption of artificial intelligence technology among accounting students in Palembang City.